At-sea behaviour in marine birds: a life-history perspective - Shoji, A (2014)
Recent bio-logging technology and associated techniques have uncovered the distribution, behaviour, and phenology of marine predators at remote locations, providing us with insights of not only scientific merit, but also in terms of conservation and management. This thesis explores the at-sea behaviour of marine birds using field studies and ethoinformatic approaches by using multiple data loggers, focusing on four species of free-ranging seabirds breeding in the UK. Key findings and conclusions are: Extending travel distance in central place foragers in the wild is associated with higher prey quality as estimated by an indirect method based on dive profiles. This result is consistent with a prediction of optimal foraging theory, but my results show empirically that seabirds are able to increase reward with distance at the extended scale of the marine environment. Razorbills Alca torda are capable of adjusting their foraging behaviour in response to proximate environmental conditions. The potential mechanisms underlying this adaptive behaviour are independent of breeding stage, but the magnitude of flight orientation is scale-dependent. These results suggest that Razorbills are capable of optimising their foraging adaptively, possibly reading cues from the environment or conspecifics. Diving behaviour in sympatric Atlantic Puffins Fratercula arctica and Razorbills is very similar, in contrast to the predictions of the competitive exclusion principle. They are likely to be near carrying capacity for the location and this may explain why Skomer’s Razorbill population is declining while its puffin population is stable. Differences in foraging trip duration of chick-rearing Manx Shearwaters Puffinus puffinus reflect differences in resource allocation between provisioning offspring and self-feeding. I developed a model based on patch quality and travel time to show that birds should use bimodal foraging trip durations to optimise feeding rates for their offspring. Individual reproductive performance in Manx Shearwaters can be predicted from previous breeding phenology and is linked to differences in overwintering behaviour patterns. This carry-over effect reveals the existence of a trade-off between current parental investment and future reproductive performance.